1989
DOI: 10.4197/sci.1-1.6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Various Nuts Stored in Commercial Markets in Jeddah

Abstract: Microbiological and chemical studies have been carried on some widely consumed nuts stored in leddah markets. Results indicated that mould count was generally higher than bacterial count specially on shelled nuts. Walnuts showed the highest average of microbial contamination including mould, bacteria, proteolytic and lipolytic microorganisms comparing with other kinds of nuts. While the lowest counts were found to be on pistachio-nuts and cashewnuts even shelled or unshelled. Mould isolates occurring most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…was isolated from almost all the samples used in this study. This result correlates with the result of many investigations on seed pathology (Sejiny, Thabet, & Elshaieb, ). In addition, Aspergillus and Penicillium spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…was isolated from almost all the samples used in this study. This result correlates with the result of many investigations on seed pathology (Sejiny, Thabet, & Elshaieb, ). In addition, Aspergillus and Penicillium spp.…”
Section: Discussionsupporting
confidence: 89%
“…Pitt, Hocking, Bhudhasamai, Miscamble, and Wheeler (1993) reported that the predominant fungi infecting peanuts collected from the was isolated from almost all the samples used in this study. This result correlates with the result of many investigations on seed pathology (Sejiny, Thabet, & Elshaieb, 1989). In addition, Aspergillus and Penicillium spp.…”
Section: Moisture Contentsupporting
confidence: 89%